The Health Impact of, and access to, New Drugs in Korea - Frank Lichtenberg (East Asian Economic Review (EAER), 2020)
We perform an econometric assessment of the role that pharmaceutical innovation— the introduction and use of new drugs—has played in improving the health of Koreans, by investigating whether diseases for which more new drugs were launched had larger subsequent increases in longevity and smaller subsequent increases in hospitalization. Drugs launched during 1993-2012 are estimated to have increased mean age at death from all diseases by 1.71 years between 1995 and 2015 and 1.09 years between 2005 and 2015. We also estimate that new drugs increased the five-year relative survival rate from all cancers combined by 23.2 percentage points—78.5% of the total increase—between 1993-1995 and 2011-2015, and that new drugs launched during 2008-2010 reduced the number of hospital days in 2017 by 13.0 million. If the drugs launched during 2003-2012 had had no effect on other medical expenditure in 2015, the cost per life-year gained would not have exceeded 6332 USD. Therefore, even if we ignore the effect of new drugs on hospital utilization, the drugs launched during 2003-2012 were very cost–effective, overall. When reduced hospital utilization is accounted for, the evidence indicates that, in the long run, pharmaceutical innovation was cost-saving as well as life-year saving.
Keywords: J11; L65; O33; 330; Longevity; Pharmaceutical; Innovation; Korea; Hospitalization; Cancer